Andrographolide, a Natural Antioxidant: An Update - Eugenie Mussard; Annabelle Cesaro; Eric Lespessailles; Brigitte Legrain; Sabine Berteina-Raboin; Hechmi Toumi (MDPI AG, 2019)
Traditionally, Andrographis paniculata has been used as an herbal remedy for lung infection treatments. Its leaves contain a diterpenoid labdane called andrographolide responsible for a wide range of biological activities such as antioxidant, anti-inflammatory, and anti-cancer properties. This manuscript is a brief review of the antioxidant mechanisms and the regulation of the Nrf2 (nuclear factor (erythroid-derived 2)-like 2) signaling pathway by andrographolide.